Radiotherapy after radical prostatectomy: treatment recommendations differ between urologists and radiation oncologists - Lavallée, Luke T; Fergusson, Dean; Mallick, Ranjeeta; Grenon, Renée; Morgan, Scott C; Momoli, Franco; Witiuk, Kelsey; Morash, Chris; Cagiannos, Ilias; Breau, Rodney H (Université d'Ottawa | University of Ottawa, 2013)
There is no consensus on optimal use of radiotherapy following radical prostatectomy. The purpose of this study was to describe opinions of urologists and radiation oncologists regarding adjuvant and salvage radiotherapy following radical prostatectomy.